Parallel Salam Contract Innovation for Agricultural Products at Bank Syariah Indonesia (BSI) Serang Branch, Banten - Amalia Muazzah Adawiah; Cucu Susilawati; Yadi Janwari (el-Jizya: Jurnal Ekonomi Islam, 2025)
This study explores the innovation of parallel salam contracts as a solution for Sharia financing in the agricultural sector. Parallel salam contracts allow for advance payments for goods to be delivered in the future, thus providing farmers with initial capital. The approach used is qualitative with descriptive-analytical methods involving literature studies, interviews, and observations of financing practices in Islamic financial institutions (IFIs). The study results indicate that this contract innovation can increase financing flexibility, operational efficiency of IFIs, and compliance with Sharia principles. However, there are challenges in the form of operational risks, uncertainty in the quality and time of delivery of goods, and the need for supporting regulations. With good risk management, adoption of digital technology, and collaboration with the agricultural sector, parallel salam contracts can accelerate Sharia financial inclusion in Indonesia. In conclusion, parallel salam contracts have great potential as an innovative financing alternative in the agricultural sector. Regulatory support, socialization, and technological infrastructure are needed for the successful widespread implementation of this contract. This study significantly contributes to developing Sharia financial products based on market needs and Sharia principle